Female Sexual Dysfunction among Women Attending the Family Planning Clinic at Aminu Kano Teaching Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Female sexual dysfunction (FSD) is a multifactorial condition in which individuals fail to experience satisfaction from sexual activity. Discussion on sexual function has been the subject extreme secretiveness due to cultural and religious reasons. There is paucity of data on the prevalence and risk factors of FSD in our environment.Objectives:To determine the prevalence, pattern and risk factors for FSD at Aminu Kano Teaching Hospital, Kano.Methods:It was a cross-sectional study of 342 women attending the family planning clinic at AKTH. The FSFI questionnaire was used to determine the prevalence and pattern of FSD among the patients. A section was added to the questionnaire to obtain information on the sociodemographic characteristics of the patients and the risk factors. The data was analysed using SPSS version 20.0. Chi square test and Fisher's exact test were used to test for association, a p-value of less than 0.05 was considered statistically significant.Results:The prevalence of FSD was found to be 86.0%. The most prevalent type of disorder was that of desire occurring in 91.8%, followed by disorders of lubrication (84.8%), arousal (80.7%), pain (66.4%), orgasm (41.5%) and satisfaction (31.6%). Only coital frequency (P